Angielski przekład Pana Tadeusza i jego polskie echa - Budrewicz, Aleksandra (Poznańskie Studia Polonistyczne. Seria Literacka, 2016)
The article discusses a variety of opinions related to the first English translation of Adam Mickiewicz’s poem Pan Tadeusz published in 1885 by Maud Ashurt Biggs (1857-1933). The main point for the author is to analyse the scope of the Polish critics’ opinions and attitudes towards this translation. Some of them were issued by well-known experts in literary translation at the time (for example Stanisław Tarnowski), as well as critics who regularly published notes on British literature and culture in Polish periodicals (Edmund Naganowski). The article points out that the translation of Pan Tadeusz triggered neither numerous, nor enthusiastic reviews; it did, however, contribute to the publication of several interesting reflections related to poetry translation.